Editor Notice about Retracted article - Štikonas, Artūras (Lietuvos matematikos rinkinys, 2025)
This article [1] has been retracted by the editor due to incomplete authorship confirmation procedures at the time of publication. The retraction does not reflect concerns regarding the scientific content of the article. [1] https://doi.org/10.15388/LMR.2025.44495